Indian Priest - (:unkn) unknown (My University, 2008)
Hand painted image of an East Indian holy man. Postcard number 321465.
Colour: White, Red, and Green Hues; Style: Portrait; Other: Unbordered, Divided
Keywords: Postcards; Hindu priests--Trinidad and Tobago; East Indians--Trinidad and Tobago; Ethnic costume--India; Men--Trinidad and Tobago; Turbans--India; Headgear--India; Clothing and dress--Trinidad and Tobago; Trinidad and Tobago; Necklaces--India; Shoes--Trinidad and Tobago; Bracelets--India; Rings--India